Development of Nanostructured Metal Based Electrocatalyst for Electrochemical Reduction of Carbon Dioxide to Alcohols - Dongare, Saudagar Balasaheb (My University, 2021)
Carbon dioxide (CO2) is a most common greenhouse gas in our planet. Unfortunately, with the intensified industrial activities by mankind and global consumption of fossil fuels (~ 81.5% of global energy resources) more CO₂ is released to the environment, causing earth–carbon imbalance, leading to possible global warming and climate change issue. In addition, increasing the CO2 concentration in the atmosphere is resulting in ocean acidification and influencing the growth of many aquatic species present in the ocean. Therefore, the reduction of the CO2 emissions and the conversion of CO2 into useful products seem to be important, indeed essential, for the conservation of the environment. Among several existing methods available for CO2 utilization, electrochemical CO2 reduction (ECO2R) has attracted increasing interest in recent years, because it is easily controlled by electrode potential and operated at ambient conditions. Also, electrical energy required to drive ECO2R can be generated from renewable sources (like geothermal power, wind, tidal, and solar) which help to achieve net-zero carbon footprints. However, CO2 is a very stable molecule and huge negative potentials are required for triggering ECO2R reaction. Many useful products like acids, ethers, and alcohols can be derived from ECO2R but in this work, high energy density products such as alcohols have been targeted due to its application in gasoline blends for fuel. Efficient electro-catalyst is needed which can control the multi-electron and multi-proton transfer pathways for ECO2R at low over-potential and can also provide high selectivity for alcohols. Therefore, the overall objective of the current Ph.D. work is to develop metal based electro-catalyst for reduction of carbon dioxide to alcohols. To achieve this objective, series of Cu based electro-catalysts were prepared by different techniques. The ECO2R performance was tested in H-type electrochemical cell in aqueous 0.1 M KHCO3 electrolyte after being characterized through in-situ and ex-situ characterization methods. The in-situ methods involved characterization using cyclic voltammetry (CV), linear sweep voltammetry (LSV), etc. and the ex-situ characterizations included transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray diffraction (XRD), X-ray photo-electron spectroscopy (XPS), and Brunauer-Emmett-Teller (BET) method, etc. The liquid products generated after ECO2R were quantified using high performance liquid chromatography (HPLC), and proton nuclear magnetic resonance (1H NMR) and the performances were measured in terms of selectivity (Faradaic efficiency), activity (current density), long term stability, etc. In the first study, highly stable metallic copper nanoparticles (Cu NPs) have been synthesized by wet chemical reduction method. The prepared Cu NPs exhibit porous morphology in pure metallic state with high surface area of 630 m2 g-1. The total Faradaic efficiency (FE) for the liquid products reached to ∼58 % at -0.8 V (vs. RHE) using prepared Cu NPs as an electro-catalyst. In addition, FE for formic acid remained constant around ∼40% at −0.8 V (vs. RHE) when reusing the same electrode number of times. The good performance of Cu NPs might be due to the presence of lots of micropores on the surface, which increases CO2 adsorption for its conversion to chemicals. In the second study, the nanostructured electro-catalyst consisting of N-doped graphene (NGN) supported Cu nanoparticles (Cu NPs) were prepared and tested for ECO2R. The electro-catalyst was optimized for loading of Cu NPs on NGN. Results show that the Cu20/NGN (20 wt. % Cu loading on NGN) catalyst showed the highest activity for ECO2R in the entire potential range studied. It gives a total 54 % FE at -1.0 V (vs. RHE) for the liquid products. The study also demonstrated that the electronic and structural properties of the electrode were improved by the addition of Cu NPs on NGN surface, which in turn enhanced the performance of the catalyst as confirmed by potential-controlled electro-catalysis. Further, oxide derived bimetallic CuZnx electro-catalysts have been suggested as alternatives for achieving high selectivity for different valuable products. Therefore, in the third study, co-precipitation approach was used to prepare CuO with various quantities of ZnO dopants (x = 5, 10, 15 and 20 wt.%). Amongst studied electro-catalysts, the highest FE of 22.27 % was obtained using CuO-ZnO10 at -0.80 V (vs. RHE) with the production rate of about 121 µmol h-1 L-1. The optimized electrode (CuO-ZnO10) showed long term stability for at least 12 h. Post characterization of the catalyst was also conducted to obtain an insight into the active sites, which indicated that CO2 reduction took place on reduced oxide sites (i.e. metallic sites) rather than on metal oxides. In the fourth study, the oxide-derived Cu and Zn nanoparticles supported on N-doped graphene (CuZnx/NGN) were prepared and ZnO loading was optimized for efficient ECO2R to multi-carbon products. Results suggest that the FE for multi-carbon products could be tuned by varying the loading of Zn in the CuZnx/NGN. The catalyst with 20 wt.% ZnO loading (CuZn20/NGN) gave the highest FE of 34.25 % for ethanol production and 12.38 % for N-propanol at -0.8 V (vs. RHE) with the total CD of 3.95 mA cm-2. The CuZn20/NGN electrode showed long term stability of at least 24 hours at optimized conditions. It is suggested that CO generated at the reduced ZnO nanoparticles increases the local surface coverage of *CO on the reduced CuO, which improves the C-C coupling rate, facilitating the multi-carbon production (i.e. ethanol). Fig. 1 shows the overall thesis outline. Overall, these studies demonstrate that the activity and selectivity of CO2 reduction electro-catalysts can be tuned by modifying the elemental composition of the electro-catalyst.
Keywords: CO2 mitigation; CO2 reduction; Electrochemistry; Ethanol; Faradaic efficiency; Fuel additive